1995
DOI: 10.1177/096368979500400303
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Porcine Hepatocyte Spheroids for use in a Bioartificial Liver

Abstract: Xenogeneic hepatocytes have recently been used in a bioartificial liver device as a potential short-term extracorporeal support of acute liver failure. Scaling up the system requires large quantities of viable and highly active cells. Hepatocytes grown as spheroids manifest higher metabolic activities for longer time periods as compared to those in monolayer cultures. Use of hepatocyte spheroids for application in a bioartificial liver can possibly alleviate the need of scaling up. Porcine hepatocytes when cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Spheroids have been widely used in tissue engineering, bioartificial livers, and embryoid body formation in stem cell research as they have been shown to improve the viability, function, and tissue-specific gene expression of several cultured primary cells (Abu-Absi et al 2002;Fukuda et al 2004;Kale et al 2000;Kelm and Fussenegger 2004;Korff and Augustin 1998;Landry et al 1985;Lazar et al 1995;Narayanan et al 2002;O'Brien et al 2002). All these applications demand reliable culture conditions for the efficient production of large quantities of spheroids with a uniform size, high cell viability, and proper cell-cell organization.…”
Section: Discussionmentioning
confidence: 99%
“…Spheroids have been widely used in tissue engineering, bioartificial livers, and embryoid body formation in stem cell research as they have been shown to improve the viability, function, and tissue-specific gene expression of several cultured primary cells (Abu-Absi et al 2002;Fukuda et al 2004;Kale et al 2000;Kelm and Fussenegger 2004;Korff and Augustin 1998;Landry et al 1985;Lazar et al 1995;Narayanan et al 2002;O'Brien et al 2002). All these applications demand reliable culture conditions for the efficient production of large quantities of spheroids with a uniform size, high cell viability, and proper cell-cell organization.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous mitochondria and lipid droplets were observed in the cytoplasm of several cells, similar to the interior structure of spheroids formed by attachment (Peshwa et al 1996) or by stirring in a spinner flask (Lazer et al 1995). Morphological characteristics predominant in spheroids were junctional complexes such as bile-canaliculus like structures between hepatocytes.…”
Section: Spheroid Morphology Under Electron Microscopementioning
confidence: 66%
“…Similar to the spheroids formed by surface attachment culture (Peshwa et al 1996) or suspension culture (Lazer et al 1995), spheroids formed by addition of collagen possess an intricate continuous bile canalicular-like network, which serves as open structures to facilitate diffusion of nutrients and waste products. These hepatocyte spheroids maintained not only viabilities but also liver-specific functions for at least 8 days.…”
Section: Discussionmentioning
confidence: 99%
“…With this pre-transplant cultivation the freshly isolated hepatocytes are stimulated to form neotissue. Therefore, the liver tissue specific hepatocytes assembly will be already initiated in vitro [30, 54]. As a biodegradable polymer scaffold, we chose PLLA, with its highly porous structure offering a favorable environment for the hepatocytes.…”
Section: Discussionmentioning
confidence: 99%